Investments in tuberculosis research – what are the gaps?. Issue 1 (December 2016) - Khan, Mishal; Fletcher, Helen; Coker, Richard
Abstract Through decades of research, numerous studies have generated robust evidence about effective interventions for tuberculosis control. Yet, the global annual decline in incidence of approximately 1 % is evidence that current approaches and investment strategies are not sufficient. In this article, we assess recent tuberculosis research funding and discuss two critical gaps in funding and in scientific evidence from topics that have been left off the research priority agenda. We first examine research and development funding goals in the 2011–2015 Global Plan to Stop Tuberculosis and analyze disbursements to different research areas by funders worldwide in 2014. We then summarize, through a compilation of published literature and consultation with 35 researchers across multiple disciplines in the London School of Hygiene and Tropical Medicine TB Centre, priorities identified by the tuberculosis research community. Finally, we compare researchers' priority areas to the global funding agendas and activities. Our analysis shows that, among the five key research areas defined in the 2011–2015 Global Plan - namely drugs, basic science, vaccines, diagnostics and operational research - drug discovery and basic science onMycobacterium tuberculosis accounted for 60 % of the $2 billion annual funding target. None of the research areas received the recommended level of funding. Operational research, which had the lowest target, received 66 % of its target funding, whereas new diagnostics received only 19 %. Although many of the priority research questions identified by researchers fell within the Global Plan categories, our analysis highlights important areas that are not explicitly mentioned in the current plan. These priority research areas included improved understanding of tuberculosis transmission dynamics, the role of social protection and social determinants, and health systems and policy research. While research priorities are increasingly important in light of the limited funding for tuberculosis, there is a risk that we neglect important research areas and encourage the formation of research silos. To ensure that funding priorities, researchers' agendas and national tuberculosis control policies are better coordinated, there should be more, and wider, dialogue between stakeholders in high tuberculosis burden countries, researchers, international policymakers and funders.